What Counts for Academic Productivity in Research Universities? - Altbach, Philip G. (International Higher Education, 2015)
Measuring research productivity in universities is a complicated and problematic process. Yet, such measurements are important for calculating the productivity of institutions, individual researchers, and academic systems. They count for a lot in the rankings. Current measures undercount the social sciences and humanities, and don’t pay sufficient attention to books. Further, the ways that knowledge is communicated is changing.